Eksistensi Negara Berdaulat Tuvalu Dengan Pindahnya Wilayah Negara Ke Metaverse - Aloysius A. Pabubung; Ninon Melatyugra (Jurnal Interpretasi Hukum, 2025)
The development of digital technology has created new phenomena in international relations, one of which is the idea of Tuvalu, which plans to move its country to the Metaverse due to the threat of its physical territory sinking as a result of climate change. This issue is important because it challenges the classical understanding of international law regarding the constitutive elements of a state, particularly defined territory as stipulated in the 1933 Montevideo Convention. In existing literature, there is no consensus between the theory of territorial state law and the practice of non-physical state digitalization, resulting in a conceptual gap between traditional sovereignty and virtual existence. This study aims to analyze whether the Metaverse can fulfill the element of territory as one of the requirements for the formation of a state and how this would imply the status of Tuvalu's sovereignty. The research method used is normative legal research with a statute approach, using the 1933 Montevideo Convention as the main basis for analysis. The results show that the Metaverse does not fulfill the element of territory in the sense of international law because it does not have definite geographical boundaries, cannot be used as a place of residence for residents, and is not subject to the principle of territorial sovereignty. Thus, Tuvalu's relocation to the Metaverse only has symbolic and cultural significance, not legal existence as a sovereign state. This study enriches international legal studies by emphasizing the importance of updating the concepts of sovereignty and territory amid advances in digital technology and the global climate crisis.